2003
DOI: 10.1128/aem.69.5.2994-2998.2003
|View full text |Cite
|
Sign up to set email alerts
|

Community-Level Physiological Profiling Performed with an Oxygen-Sensitive Fluorophore in a Microtiter Plate

Abstract: Community-level physiological profiling based upon fluorometric detection of oxygen consumption was performed on hydroponic rhizosphere and salt marsh litter samples by using substrate levels as low as 50 ppm with incubation times between 5 and 24 h. The rate and extent of response were increased in samples acclimated to specific substrates and were reduced by limiting nitrogen availability in the wells.Characterization and classification of heterotrophic microbial communities based on rapid assessment of mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 17 publications
1
32
1
2
Order By: Relevance
“…In a set of follow-up experiments, samples collected at the termination of respirometry experiments were filtered (0.45 μm) and introduced to a fresh inoculum. Oxygen uptake was not measurable for any samples either by respirometry or by a microtiter-based oxygen sensor system (Garland et al 2003) after introduction to a fresh inoculum (data not shown), further indicating that metabolites formed during biodegradation of surfactants were not readily biodegradable. Complete removal of the studied surfactants in a biological treatment system may be limited or require a large liquid retention time.…”
Section: Batch Cod Removal Assaysmentioning
confidence: 70%
“…In a set of follow-up experiments, samples collected at the termination of respirometry experiments were filtered (0.45 μm) and introduced to a fresh inoculum. Oxygen uptake was not measurable for any samples either by respirometry or by a microtiter-based oxygen sensor system (Garland et al 2003) after introduction to a fresh inoculum (data not shown), further indicating that metabolites formed during biodegradation of surfactants were not readily biodegradable. Complete removal of the studied surfactants in a biological treatment system may be limited or require a large liquid retention time.…”
Section: Batch Cod Removal Assaysmentioning
confidence: 70%
“…The reduction of redox dye and measuring the change in absorbance microplate wells after a short period of incubation (Garland, 1996, Di Salvo, García de Salamone 2008, ii. O 2 consumption on a sensitive fluorometer microplate cell (Garland et al, 2003) and iii. The production of carbon dioxide in the bottle headspace at the top of each cell (CS multi-induced respiration).…”
Section: Functionality and Microbial Diversitymentioning
confidence: 99%
“…Optical oxygen sensing is based on the principles of the quenching effect of molecular oxygen on fluorescent ruthenium(II) complexes (Gao et al, 2004;Zhong et al, 2003) or phosphorescent metal-porphyrin dyes (Papkovsky et al, 1992, allowing for the non-invasive, reversible, and continuous detection of oxygen (Alderman et al, 2004;Garland et al, 2003;Guarino Richard et al, 2004;O'Donovan et al, 2005;O'Riordan et al, 2000;Papkovsky, 1995;Wodnicka et al, 2000). In this work, we fabricated oxygen-sensitive, fluorescent nanosensors for dynamically measuring the oxygen concentration in the proximity of individual living cells.…”
Section: Introductionmentioning
confidence: 98%
“…Oxygen consumption is correlated with many physiologically relevant processes, and therefore, oxygen concentration is often used as a surrogate for certain cell characteristics, such as their viability upon exposure to cytotoxic drugs and environmental stress (Alderman et al, 2004;Land et al, 1997;Tsukatani et al, 2003), protein synthesis capability (Wieser and Krumschnabel, 2001), mitochondria function and dysfunction (Trimarchi et al, 2000), cell growth and differentiation (Stitt et al, 2002;Yamada et al, 1985), substrate oxidation and utilization capacity (Chang et al, 1995;Cui et al, 2005;Higareda et al, 1997), sensitivity to radioactive reagents (Korystov Iu, 1983), and susceptibility to antibiotics (O'Riordan et al, 2000;Wodnicka et al, 2000). Moreover, the concentration of oxygen plays an important role in the development of microbial communities and multi-cellular organisms (Garland et al, 2003). Local oxygen tension, for instance, is a key parameter for monitoring and modeling normal chondrocyte activity and extracellular matrix production during chondrogenesis (Malda et al, 2004).…”
Section: Introductionmentioning
confidence: 99%